The role of vowel length in comprehension during cross-cultural communication: An action research project - Morgan, Gareth (JOURNAL OF ADVANCES IN LINGUISTICS, 2016)
The paper describes the process and outcomes of an action research project with the aim of determining whether focusing classroom input on vowel length has a positive effect on the production and comprehension of these sounds. The statistics were generated from respondents listening to the output of speakers from an experimental group, who had received instruction on this issue, and to the output of speakers from a control group, who had not been provided with any input, with the rate of intelligibility being compared. The conclusion drawn is t